Laminate and article

A laminate with a modified polypropylene resin and urethane resin composition layers addresses the issues of insufficient barrier resistance and adhesion in existing laminates, providing improved performance for food packaging applications.

JP2024178589APending Publication Date: 2024-12-25DIC CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023096842
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-13
Publication Date
2024-12-25

AI Technical Summary

Technical Problem

Existing laminates with polyolefin resins and vapor-deposited films exhibit insufficient barrier resistance and adhesion properties, failing to meet the increasing performance requirements for applications such as food packaging.

Method used

A laminate structure comprising a base material, a modified polypropylene resin layer, and a urethane resin composition layer is developed, enhancing both barrier resistance and adhesive properties.

Benefits of technology

The laminate demonstrates excellent barrier resistance and adhesive properties, making it suitable for use as a vapor-deposited film in food packaging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024178589000001
    Figure 2024178589000001
  • Figure 2024178589000002
    Figure 2024178589000002
  • Figure 2024178589000003
    Figure 2024178589000003
Patent Text Reader

Abstract

To provide a laminate with superior barrier resistance and superior adhesion, and an article having the laminate.SOLUTION: A laminate at least includes a substrate (A), a layer (B) composed of a modified polyolefin resin, and a layer (C) composed of a urethane resin composition containing a urethane resin (c1). The layer (B) is present on the substrate (A), and the layer (C) is located on the layer (B) . Also provided is an article having the laminate.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to laminates and articles having excellent barrier resistance and adhesion properties. [Background technology]

[0002] By forming a metal vapor-deposited film on the surface of a resin film, it is possible to impart high gas barrier properties, and resin molded articles with such vapor-deposited surfaces are widely used in everyday products, such as packaging materials for foods and beverages.

[0003] The resin molded body is required to have good adhesion between the substrate and the vapor-deposited film. However, depending on the type of resin constituting the substrate, the adhesion to the vapor-deposited film may be poor. In order to improve the adhesion, for example, a formulation has been proposed in which a primer layer is provided on the substrate surface.

[0004] For example, a laminate in which a resin layer containing a polyolefin resin and a vapor-deposited film are laminated in this order on a substrate, the polyolefin resin being a polyolefin resin containing an olefin component (A) consisting of an alkene having 2 to 4 carbon atoms as a main component and containing 2 to 40 mass % of a (meth)acrylic acid ester component (B) is known in which a resin layer containing a polyolefin resin is used as a primer (see, for example, Patent Document 1). The barrier resistance and adhesion were insufficient, and the performance requirements, which have been increasing in recent years, were not satisfied.

[0005] Therefore, there is a demand for materials having excellent barrier resistance and adhesive properties. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2011-31526 A Summary of the Invention [Problem to be solved by the invention]

[0007] The problem that the present invention seeks to solve is to provide laminates and articles that have excellent barrier resistance and adhesion. [Means for solving the problem]

[0008] Means for Solving the Problems The present inventors have conducted intensive research to solve the above problems, and as a result have found that the above problems can be solved by using a laminate having at least a base material, a layer made of a modified polypropylene resin, and a layer made of a urethane resin composition, the laminate being characterized by having a specific layer structure, and have thus completed the present invention.

[0009] That is, the present invention relates to a laminate having at least a substrate (A), a layer (B) made of a modified polypropylene resin, and a layer (C) made of a urethane resin composition, characterized in that the laminate has layer (B) on the substrate (A), and layer (C) on layer (B). Effect of the Invention

[0010] The laminate of the present invention has excellent barrier resistance and adhesiveness, and can therefore be suitably used as a vapor deposition treatment film for food packaging. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The laminate of the present invention has at least a substrate (A), a layer (B) made of a modified polypropylene resin, and a layer (C) made of a urethane resin composition.

[0012] Furthermore, since the laminate of the present invention has excellent barrier resistance and adhesion, a laminate having the layer (B) on the base material (A) and the layer (C) on the layer (B) is used.

[0013] Examples of the substrate (A) include polyolefin films such as polyethylene terephthalate (PET) films, polystyrene films, polyamide films, polyacrylonitrile films, polyethylene films (LLDPE: linear low density polyethylene film, HDPE: high density polyethylene film), polypropylene films (CPP: unstretched polypropylene film, OPP: biaxially stretched polypropylene film), polyvinyl alcohol films, ethylene-vinyl alcohol copolymer films, cycloolefin copolymer films, etc. These films may or may not be stretched.

[0014] As the layer (B), a layer made of a modified polypropylene resin is used.

[0015] The modified polyolefin resin may, for example, be one that uses, as monomer units, an alkene component (b1-1) having 2 to 4 carbon atoms, a (meth)acrylic acid ester component (b1-2), and an acid-modified component (b1-3) as essential raw materials. In the present invention, "(meth)acrylic" means acrylic and / or methacrylic. Furthermore, "(meth)acrylate" means acrylate and / or methacrylate. Furthermore, "(meth)acryloyl" means acryloyl and / or methacryloyl.

[0016] Examples of the alkene component (b1-1) having 2 to 4 carbon atoms include ethylene, propylene, isobutylene, and 1-butene. These compounds can be used alone or in combination of two or more. Among these, the amount of ethylene and propylene used is preferably 80 mass% or more in total in the raw material of the modified polyolefin resin, since a laminate having excellent barrier resistance and adhesiveness can be obtained.

[0017] Examples of the (meth)acrylic acid ester component (b1-2) include methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, butyl acrylate, and butyl methacrylate. These compounds can be used alone or in combination of two or more. Among these, methyl acrylate and ethyl acrylate are preferred from the viewpoints of adhesion to the substrate and the deposition layer and industrial availability.

[0018] The acid-modified component (b1-3) may, for example, be an unsaturated carboxylic acid.

[0019] The unsaturated carboxylic acid is a compound having at least one carboxyl group or acid anhydride group in the molecule, and specific examples thereof include acrylic acid, methacrylic acid, maleic acid, maleic anhydride, itaconic acid, itaconic anhydride, fumaric acid, crotonic acid, etc., as well as half esters and half amides of unsaturated dicarboxylic acids, etc. Among these, acrylic acid, methacrylic acid, maleic acid, and maleic anhydride are preferred, and maleic anhydride is particularly preferred.

[0020] As the layer (C), a layer made of a urethane resin composition is used.

[0021] As the urethane resin composition, one containing a urethane resin (c1) is used.

[0022] The urethane resin (c1) used contains a polyol compound (c1-1) and a polyisocyanate compound (c1-2) as essential raw materials.

[0023] Examples of the polyol compound (c1-1) include polyether polyol, polyester polyol, polycarbonate polyol, polycaprolactone polyol, polyacrylic polyol, silicon-modified polyol, etc. These polyol compounds can be used alone or in combination of two or more. These polyol compounds may be derived from petrochemicals or biomass.

[0024] Examples of the polyester polyol include those obtained by subjecting a polyvalent carboxylic acid and a polyhydric alcohol to an esterification reaction.

[0025] Examples of the polycarboxylic acid include aromatic dicarboxylic acids such as phthalic acid, isophthalic acid, terephthalic acid, and naphthalenedicarboxylic acid, and esters thereof, and aliphatic dicarboxylic acids such as succinic acid, glutaric acid, adipic acid, maleic acid, pimelic acid, suberic acid, azelaic acid, itaconic acid, sebacic acid, chlorendic acid, 1,2,4-butane-tricarboxylic acid, decanedicarboxylic acid, cyclohexanedicarboxylic acid, dimer acid, and fumaric acid, and esters thereof. These polycarboxylic acids and esters thereof can be used alone or in combination of two or more.

[0026] Examples of the polyhydric alcohol include aromatic diols such as benzene dimethanol, toluene dimethanol, and xylene dimethanol, and aliphatic polyols such as ethylene glycol, propylene glycol, 1,3-propylene diol, 1,4-butanediol, 1,6-hexanediol, 1,8-octanediol, diethylene glycol, triethylene glycol, cyclohexane-1,4-diol, cyclohexane-1,4-dimethanol, and neopentyl glycol ethylene glycol. These polyhydric alcohols can be used alone or in combination of two or more.

[0027] In addition, since a laminate having excellent barrier resistance and adhesiveness can be obtained from the polyester polyol, it is preferable that the raw material contains diethylene glycol and / or ethylene glycol, and the total content of the diethylene glycol and the ethylene glycol in the raw material of the polyester polyol is preferably in the range of 9 to 40 mass %.

[0028] In the esterification reaction when producing the polyester polyol, it is preferable to use an esterification catalyst for the purpose of promoting the esterification reaction.The esterification catalyst includes, for example, metals such as titanium, tin, zinc, aluminum, zirconium, magnesium, hafnium, and germanium; metal compounds such as titanium tetraisopropoxide, titanium tetrabutoxide, titanium oxyacetylacetonate, dibutyltin oxide, dibutyltin diacetate, dibutyltin dilaurate, tin octanoate, 2-ethylhexane tin, zinc acetylacetonate, zirconium tetrachloride, zirconium tetrachloride tetrahydrofuran complex, hafnium tetrachloride, hafnium tetrachloride tetrahydrofuran complex, germanium oxide, and tetraethoxygermanium.These esterification catalysts can be used alone or in combination of two or more kinds.

[0029] The polycarbonate polyol may be, for example, a reaction product of a carbonate ester and / or phosgene with a compound having two or more hydroxyl groups.

[0030] Examples of the carbonate ester include dimethyl carbonate, diethyl carbonate, diphenyl carbonate, ethylene carbonate, propylene carbonate, etc. These carbonate esters can be used alone or in combination of two or more kinds.

[0031] Examples of the compound having two or more hydroxyl groups include ethylene glycol, propylene glycol, 1,3-propanediol, 1,4-butanediol, 1,3-butanediol, 1,2-butanediol, 2-methyl-1,3-propanediol, 1,5-pentanediol, neopentyl glycol, 1,6-hexanediol, 1,5-hexanediol, 3-methyl-1,5-pentanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,8-nonanediol, 2-ethyl-2-butyl-1,3-propanediol, 1,10-decanediol, 1,12-dodecanediol, 1,4-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, trimethylolpropane, 3-methylpentanediol, neopentyl glycol, trimethylolethane, and glycerin. These compounds can be used alone or in combination of two or more kinds.

[0032] The number average molecular weight of the polyol compound (c1-1) is preferably in the range of 500 to 5,000, since a laminate having excellent barrier resistance and adhesiveness can be obtained. In the present invention, the number average molecular weight indicates a value measured by gel permeation chromatography (GPC).

[0033] The content of the polyol compound (c1-1) in the raw material of the urethane resin (c1) is preferably in the range of 30 to 85 mass%, more preferably in the range of 50 to 85 mass%, since a laminate having excellent barrier resistance and adhesiveness can be obtained.

[0034] Examples of the polyisocyanate compound (c1-2) include aliphatic polyisocyanates such as hexamethylene diisocyanate, lysine diisocyanate, cyclohexane diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, xylylene diisocyanate, tetramethylxylylene diisocyanate, dimer acid diisocyanate, and norbornene diisocyanate; alicyclic diisocyanates such as norbornane diisocyanate, isophorone diisocyanate, hydrogenated xylylene diisocyanate, and hydrogenated diphenylmethane diisocyanate; and aromatic polyisocyanates such as phenylene diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, xylylene diisocyanate, naphthalene diisocyanate, polymethylene polyphenyl polyisocyanate, and carbodiimidized diphenylmethane polyisocyanate. These polyisocyanate compounds can be used alone or in combination of two or more kinds. Among these, toluene diisocyanate is preferred because it gives a laminate having excellent barrier resistance and adhesiveness.

[0035] The content of the polyisocyanate compound (c1-2) in the raw material of the urethane resin (c1) is preferably in the range of 15 to 70 mass%, more preferably in the range of 15 to 50 mass%, because a laminate having excellent barrier resistance and adhesiveness can be obtained.

[0036] The concentration of aromatic rings derived from the polyester polyol in the urethane resin (c1) is 1 mmol / g or more, and since a laminate having excellent barrier resistance and adhesiveness can be obtained, the concentration is preferably in the range of 2 to 4 mmol / g, and more preferably in the range of 2.5 to 3.5 mmol / g.

[0037] The urethane bond concentration of the urethane resin (c1) is preferably in the range of 1.5 to 4 mmol / g, more preferably in the range of 2 to 3 mmol / g, since a laminate having excellent barrier resistance and adhesiveness can be obtained.

[0038] The acid value of the urethane resin (c1) is preferably in the range of 15 to 45 mgKOH / g, more preferably in the range of 20 to 35 mgKOH / g, since a laminate having excellent barrier resistance and adhesiveness can be obtained.

[0039] The method for producing the urethane resin (c1) is not particularly limited, and any method may be used. For example, the urethane resin (c1) may be produced by reacting all of the reaction raw materials including the polyol compound (c1-1) and the polyisocyanate compound (c1-2) at once, or by reacting the reaction raw materials sequentially.

[0040] Regarding the reaction ratio of the polyol compound (c1-1) and the polyisocyanate compound (c1-2), the molar ratio of the number of moles of hydroxyl groups in the polyol compound (c1-1) to the number of moles of isocyanate groups in the polyisocyanate (c1-2) [(isocyanate groups) / (hydroxyl groups)] is preferably in the range of 0.7 to 2.5, and more preferably in the range of 0.9 to 1.2, since a laminate having excellent barrier resistance and adhesiveness can be obtained.

[0041] In addition, an organic solvent may be used when producing the urethane resin (c1).

[0042] Examples of the organic solvent include ketone compounds such as acetone and methyl ethyl ketone, ether compounds such as tetrahydrofuran and dioxane, acetate compounds such as ethyl acetate and butyl acetate, nitrile compounds such as acetonitrile, amide compounds such as dimethylformamide and N-methylpyrrolidone, and alcohol compounds such as methanol, ethanol, isopropyl alcohol, isobutanol, sec-butanol, and tertiary butanol. These organic solvents can be used alone or in combination of two or more kinds.

[0043] The weight average molecular weight of the urethane resin (c1) is preferably in the range of 5,000 to 100,000, and more preferably in the range of 15,000 to 80,000, since a laminate having excellent barrier resistance and adhesiveness can be obtained. The weight average molecular weight of the urethane resin (c1) is a value obtained by measuring in the same manner as the number average molecular weight of the polyol compound (c1-1).

[0044] The urethane resin composition may contain an aqueous medium (c2), an organic solvent (c3), and other additives, if necessary.

[0045] Examples of the aqueous medium (c2) include ion-exchanged water, distilled water, etc. These aqueous media can be used alone or in combination of two or more kinds.

[0046] As the organic solvent (c3), the same organic solvents as those exemplified above can be used.

[0047] When forming the layer (B) on the substrate (A), the coating layer may be formed by an in-line coating method in which an aqueous urethane resin composition is applied during a film stretching process and then a stretching process is further performed, or the coating layer may be formed by an off-line coating method in which an aqueous urethane resin composition is applied and dried after the film stretching process to form a coating layer.

[0048] Examples of the other additives include crosslinking agents, pigments, flame retardants, plasticizers, softeners, stabilizers, waxes, defoamers, dispersants, penetrating agents, surfactants, fillers, antifungal agents, antibacterial agents, ultraviolet absorbers, antioxidants, antistatic agents, weathering stabilizers, fluorescent brighteners, antiaging agents, thickeners, etc. These additives can be used alone or in combination of two or more.

[0049] The glass transition temperature of the urethane resin composition is preferably in the range of 5 to 95° C., since a laminate having excellent barrier resistance and adhesiveness can be obtained.

[0050] The surface wetting tension of the layer (C) is preferably 40 mN / m or more, since this gives a laminate having excellent barrier resistance and adhesiveness.

[0051] In the laminate of the present invention, a vapor-deposited layer (D) may be provided on the layer (C).

[0052] The deposition layer (D) is not particularly limited as long as it can provide gas barrier properties, and examples thereof include a metal deposition layer and a metal oxide deposition layer. Examples of metals used in the metal deposition layer include various metals, but aluminum, which is inexpensive and widely used, is particularly preferred. In addition, aluminum oxide (AlOx) and silicon oxide (SiOx) are preferred as the metal oxides, as they are highly versatile materials.

[0053] Examples of a method for forming the vapor deposition layer (D) on the layer (C) include known methods such as physical vapor deposition methods (PVD methods) such as vacuum deposition, sputtering, and ion plating, chemical vapor deposition methods (CVD methods) such as plasma enhanced chemical vapor deposition and thermal chemical vapor deposition, and plating deposition.

[0054] The article of the present invention includes the laminate, and examples thereof include packaging materials. EXAMPLES

[0055] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to the examples given below.

[0056] The number average molecular weight of the polyester polyols used in the examples and comparative examples is a value measured by gel permeation chromatography (GPC) under the following conditions.

[0057] Measurement equipment: High-speed GPC equipment (Tosoh Corporation "HLC-8220GPC") Column: The following columns manufactured by Tosoh Corporation were used, connected in series. "TSKgel G5000" (7.8mm I.D. x 30cm) x 1 "TSKgel G4000" (7.8mm I.D. x 30cm) x 1 "TSKgel G3000" (7.8mm I.D. x 30cm) x 1 "TSKgel G2000" (7.8mmI.D. x 30cm) x 1 Detector: RI (differential refractometer) Column temperature: 40℃ Eluent: tetrahydrofuran (THF) Flow rate: 1.0mL / min Injection volume: 100 μL (sample concentration 0.4% by mass in tetrahydrofuran solution) Standard sample: A calibration curve was prepared using the following standard polystyrene.

[0058] (Standard polystyrene) "TSKgel Standard Polystyrene A-500" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene A-1000" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene A-2500" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene A-5000" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-1" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-2" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-4" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-10" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-20" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-40" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-80" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-128" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-288" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-550" manufactured by Tosoh Corporation

[0059] (Synthesis Example 1: Synthesis of polyester polyol (1)) In a polyester reaction vessel equipped with a stirrer, a nitrogen gas inlet tube, a distillation tube, a water separator, etc., 520 parts by mass of phthalic anhydride, 480 parts by mass of diethylene glycol, and 0.05 parts by mass of titanium tetraisopropoxide were charged, and the vessel was gradually heated so that the temperature at the top of the distillation tube did not exceed 100° C., and the internal temperature was maintained at 220° C. When the acid value became 10 mgKOH / g or less, heating was continued under a reduced pressure of 100 torr, and when the acid value became 1 mgKOH / g or less, the esterification reaction was terminated, and a polyester polyol (1) having a number average molecular weight of 985 was obtained.

[0060] (Synthesis Example 2: Synthesis of polyester polyol (2)) In a polyester reaction vessel equipped with a stirrer, a nitrogen gas inlet tube, a distillation tube, a water separator, and the like, 318 parts by mass of terephthalic acid, 318 parts by mass of isophthalic acid, 134 parts by mass of ethylene glycol, 230 parts by mass of diethylene glycol, and 0.05 parts by mass of titanium tetraisopropoxide were charged, and the mixture was gradually heated so that the temperature at the top of the distillation tube did not exceed 100° C., and the internal temperature was maintained at 220° C. When the acid value became 10 mgKOH / g or less, heating was continued under reduced pressure of 100 torr, and when the acid value became 1 mgKOH / g or less, the esterification reaction was terminated, and a polyester polyol (2) having a number average molecular weight of 1,700 was obtained.

[0061] (Synthesis Example 3: Synthesis of polyester polyol (3)) In a polyester reaction vessel equipped with a stirrer, a nitrogen gas inlet tube, a distillation tube, a water separator, etc., 354 parts by mass of isophthalic acid, 78 parts by mass of adipic acid, 180 parts by mass of sebacic acid, 62 parts by mass of ethylene glycol, 208 parts by mass of neopentyl glycol, 118 parts by mass of hexamethylene glycol, and 0.05 parts by mass of titanium tetraisopropoxide were charged, and the temperature at the top of the distillation tube was gradually heated so as not to exceed 100° C., and the internal temperature was maintained at 220° C. When the acid value became 10 mgKOH / g or less, heating was continued under reduced pressure of 100 torr, and the esterification reaction was terminated when the acid value became 1 mgKOH / g or less, to obtain a polyester polyol (3) having a number average molecular weight of 2000.

[0062] The compositions of the polyester polyols (1) to (3) obtained in Synthesis Examples 1 to 3 are shown in Table 1.

[0063] [Table 1]

[0064] (Synthesis Example 4: Synthesis of Water-Based Urethane Resin Composition (1)) In a four-neck flask equipped with a thermometer, a stirrer, a reflux condenser and a nitrogen inlet tube, 124 parts by mass of polyester polyol (1) obtained in Synthesis Example 1, 11 parts by mass of 2,2-dimethylolpropionic acid (DMPA), 139 parts by mass of methyl ethyl ketone were added, and then 36 parts by mass of tolylene diisocyanate were added, and the mixture was reacted at 75°C for 8 hours. Then, the mixture was cooled to 50°C, and 8.5 parts by mass of triethylamine were added to neutralize the mixture to obtain a urethane resin. Then, 682 parts by mass of ion-exchanged water was added to make the mixture water-soluble. After removing methyl ethyl ketone from the obtained transparent reaction product at 40 to 60°C under reduced pressure, ion-exchanged water was added to adjust the concentration, and a stable aqueous urethane resin composition (1) with a non-volatile content of 23% by mass was obtained.

[0065] (Synthesis Example 2: Synthesis of Water-Based Urethane Resin Composition (2)) An aqueous urethane resin composition (2) was obtained in the same manner as in Example 1, except that the polyester polyol used in Example 1 was changed to one shown in Table 2.

[0066] The compositions of the aqueous urethane resin compositions (1) and (2) obtained in Synthesis Examples 4 and 5 are shown in Table 2.

[0067] [Table 2]

[0068] (Synthesis Example 6: Preparation of Coating Composition (B-1) for Layer (B)) A coating composition (B-1) for layer (B) having a non-volatile content of 10% was obtained by diluting 10 parts by mass (2.52 parts by mass as solid content) of a modified polyolefin resin ("Arrowbase DA-5010N" manufactured by Unitika Ltd., non-volatile content 25.2%) with water.

[0069] (Synthesis Example 7: Preparation of Coating Composition (B-2) for Layer (B)) A coating composition (B-1) for layer (B) having a non-volatile content of 10% was obtained by diluting 10 parts by mass (2.64 parts by mass as solid content) of a modified polyolefin resin ("Arrowbase SB-1030N" manufactured by Unitika Ltd., non-volatile content 26.4%) with water.

[0070] (Synthesis Example 8: Preparation of Coating Composition (C-1) for Layer (C)) 10 parts by mass (2.3 parts by mass as solids) of the aqueous urethane resin composition (1) having a non-volatile content of 23% obtained in Synthesis Example 4 was diluted with water to obtain a coating composition (C-1) for layer (C) having a non-volatile content of 10%.

[0071] (Synthesis Example 9: Preparation of Coating Composition (C-2) for Layer (C)) 10 parts by mass of the aqueous urethane resin composition (1) having a non-volatile content of 23% obtained in Synthesis Example 4 (2.3 parts by mass as solid content) and 0.9 parts by mass of the crosslinking agent (1) ("Carbodilite SV-02" manufactured by Nisshinbo Chemical Inc., non-volatile content 40%) were mixed and diluted with water to obtain a coating composition (C-2) for layer (C) having a non-volatile content of 10%.

[0072] (Synthesis Example 10: Preparation of Coating Composition (C-3) for Layer (C)) 10 parts by mass of the aqueous urethane resin composition (1) having a non-volatile content of 23% obtained in Synthesis Example 4 (2.3 parts by mass as solid content) and 0.6 parts by mass of a crosslinking agent (2) ("Bayhydur ultra 3100" manufactured by Sumika Covestro Urethane Co., Ltd., non-volatile content 100%) were mixed and diluted with water to obtain a coating composition (C-3) for layer (C) having a non-volatile content of 10%.

[0073] (Synthesis Example 11: Preparation of Coating Composition (C-4) for Layer (C)) 10 parts by mass (2.3 parts by mass as solids) of the aqueous urethane resin composition (2) having a non-volatile content of 23% obtained in Synthesis Example 5 was diluted with water to obtain a coating composition (C-4) for layer (C) having a non-volatile content of 10%.

[0074] (Synthesis Example 12: Preparation of Coating Composition (C-5) for Layer (C)) 10 parts by mass of the aqueous urethane resin composition (2) having a non-volatile content of 23% (2.3 parts by mass as solid content) obtained in Synthesis Example 5 and 0.9 parts by mass of the crosslinking agent (1) were mixed and diluted with water to obtain a coating composition (C-2) for layer (C) having a non-volatile content of 10%.

[0075] (Synthesis Example 13: Preparation of Coating Composition (C-6) for Layer (C)) 10 parts by mass of the aqueous urethane resin composition (2) having a non-volatile content of 23% (2.3 parts by mass as solid content) obtained in Synthesis Example 5 and 0.6 parts by mass of the crosslinking agent (2) were mixed and diluted with water to obtain a coating composition (C-6) for layer (C) having a non-volatile content of 10%.

[0076] (Synthesis Example 14: Preparation of Coating Composition (C-7) for Layer (C)) 10 parts by mass (2.3 parts by mass as solids) of the aqueous urethane resin composition (1) having a non-volatile content of 23% obtained in Synthesis Example 4 and 9.1 parts by mass (2.26 parts by mass as solids) of a modified polyolefin resin ("Arrowbase DA-5010N" manufactured by Unitika Ltd., non-volatile content 25.2%) were mixed and diluted with water to obtain a coating composition (C-7) for layer (C) having a non-volatile content of 10%.

[0077] (Synthesis Example 15: Preparation of Coating Composition (C-8) for Layer (C)) 10 parts by mass (2.3 parts by mass as solid content) of the aqueous urethane resin composition (1) having a non-volatile content of 23% obtained in Synthesis Example 4 and 21.3 parts by mass (5.37 parts by mass as solid content) of a modified polyolefin resin ("Arrowbase DA-5010N" manufactured by Unitika Ltd., non-volatile content 25.2%) were mixed and diluted with water to obtain a coating composition (C-8) for layer (C) having a non-volatile content of 10%.

[0078] (Example 1: Preparation of laminate (1)) The coating composition (B-1) for layer (B) obtained in Synthesis Example 6 was applied to the corona-treated surface of the substrate FOR (Futamura Chemical Co., Ltd., "FOR#20", biaxially oriented polypropylene film) using a bar coater #5 in an amount of 0.5 g / m 2 (solid content) and placed in a dryer set to 80° C. for 30 seconds to obtain a film having a uniform coating layer (coating film; layer (B)).

[0079] Next, the coating composition (C-1) for layer (C) obtained in Synthesis Example 8 was applied to the surface of the coating layer using a bar coater #5 in an amount of 0.5 g / m 2 (solid content) and placed in a dryer set at 80° C. for 30 seconds to obtain a laminate (1) having layer (C) on layer (B).

[0080] (Examples 2 to 12: Preparation of Laminates (2) to (12)) Laminates (2) to (12) were obtained in the same manner as in Example 1, except that the coating composition for layer (B) and the coating composition for layer (C) were changed to those shown in Tables 3 and 4, respectively.

[0081] (Example 13: Preparation of laminate (13)) The coating composition (B-1) for layer (B) obtained in Synthesis Example 6 was applied to the unstretched polypropylene film as the substrate by in-line coating to obtain a laminate (13) in the same manner as in Example 1. The coating by the in-line coating method is specifically a method in which pellets (homopolymer) of polypropylene (hereinafter abbreviated as "PP") are fed to a single-screw extruder, heated and melted at 250°C, and extruded into a sheet on a cooling roll at 45°C to obtain an unstretched PP film, which is then heated to 140°C and stretched 5 times in the longitudinal direction to obtain a uniaxially stretched PP film, and the coating composition (B-1) for layer (B) obtained in Synthesis Example 6 was applied to the uniaxially stretched film by reverse coating. Thereafter, the film was stretched 8 times in the short direction at 160° C., and then heat-set by heating at 180° C. for 30 seconds to obtain a laminate in which the layer (B) was placed on the base material (PP).

[0082] (Comparative Examples 1 to 9: Preparation of Laminates (R1) to (R9)) Laminates (R1) to (R9) were obtained in the same manner as in Example 1, except that the coating composition for layer (B) and the coating composition for layer (C) were changed to those shown in Table 5, respectively.

[0083] The laminates (1) to (13) and (R1) to (R9) obtained in the above examples and comparative examples were used to carry out the following evaluations.

[0084] [Preparation of evaluation laminate film (1)] Aluminum was deposited by vacuum deposition on the surface of the laminate obtained in each of the examples and comparative examples (i.e., the surface of layer (C)) to obtain a deposition film having each deposition layer. Next, DiCdry LX-703VL (a solvent-based polyester polyol manufactured by DIC Graphics) and KR-90 (a polyisocyanate crosslinking agent manufactured by DIC Graphics) were mixed in a mass ratio of 15 / 1, and ethyl acetate was added so that the non-volatile content was 30% to prepare an adhesive. The adhesive was applied to the surface of the deposition layer of the deposition film in an amount of 3.0 g / m using a bar coater. 2 The solvent was evaporated using hot air at 80°C from a dryer to form an adhesive layer on the deposition layer. Next, a CPP film ("RXC-22", 50 μm thick, manufactured by Mitsui Chemicals Tohcello Inc.) was dry laminated at a temperature of 40°C, a pressure of 0.4 MPa, and a lamination speed of 40 m / min to obtain a laminated film. This laminated film was left to stand in a dryer set at a temperature of 40°C for 3 days to dry and harden, obtaining a laminated film for evaluation (1).

[0085] [Preparation of evaluation laminate film (2)] Alumina oxide was deposited by vacuum deposition on the surface of the laminate obtained in each of the examples and comparative examples (i.e., the surface of layer (C)) to obtain a deposition film having each deposition layer. Next, DiCdry LX-703VL (a solvent-based polyester polyol manufactured by DIC Graphics) and KR-90 (a polyisocyanate crosslinking agent manufactured by DIC Graphics) were mixed in a mass ratio of 15 / 1, and ethyl acetate was added so that the non-volatile content was 30% to prepare an adhesive. The adhesive was applied to the surface of the deposition layer of the deposition film in an amount of 3.0 g / m using a bar coater. 2 The solvent was evaporated using hot air at 80°C from a dryer to form an adhesive layer on the deposition layer. Next, a CPP film ("RXC-22", 50 μm thick, manufactured by Mitsui Chemicals Tohcello Inc.) was dry laminated at a temperature of 40°C, a pressure of 0.4 MPa, and a lamination speed of 40 m / min to obtain a laminated film. This laminated film was left to stand in a dryer set at a temperature of 40°C for 3 days to dry and harden, obtaining a laminated film for evaluation (2).

[0086] [Method of evaluating barrier resistance] In the present invention, the barrier resistance was evaluated by measuring the oxygen transmission rate.

[0087] The evaluation laminate films (1) and (2) were each measured for oxygen permeability (cc / (m) in an atmosphere of 23°C x 0% RH (relative humidity) in accordance with JIS-K7126 (constant pressure method) using "M8101" manufactured by Illinois Corporation. 2 ·day·atm) was measured.

[0088] [Method of evaluating adhesion] In the present invention, the adhesiveness was evaluated by measuring the laminate adhesive strength.

[0089] The laminated films (1) and (2) for evaluation were each cut to a width of 15 mm in the coating direction, and the laminated films were peeled in a 180° direction at an atmospheric temperature of 23° C. and a peeling speed of 300 mm / min using a tabletop precision universal testing machine (Shimadzu Corporation's "Autograph AGS-X"), and the tensile strength was determined as the laminate strength when the laminated films were peeled in a 180° direction. The unit of laminate strength was N / 15 mm.

[0090] The adhesive strength is preferably 1.0 N / 15 mm or more, more preferably 1.5 N / 15 mm or more, and particularly preferably 2.5 N / 15 mm or more.

[0091] Tables 3 and 4 show the configurations and evaluation results of the laminates (1) to (13) and (R1) to (R9) obtained in the above examples and comparative examples.

[0092] [Table 3]

[0093] [Table 4]

[0094] [Table 5]

[0095] From the evaluation results in Tables 3 and 4 above, it was confirmed that the laminate of the present invention has excellent barrier resistance and adhesiveness.

[0096] On the other hand, Comparative Examples 1 and 2 shown in Table 5 are examples of laminates not having layer (C). Since the surface to be vapor-deposited is a modified polyolefin layer, which is non-polar, it has low affinity with the vapor-deposited layer, and it was confirmed that the oxygen permeability after vapor deposition was significantly deteriorated.

[0097] In Comparative Examples 3 to 7, which are examples of laminates not having layer (B), it was confirmed that the adhesive strength after deposition was reduced due to reduced adhesiveness to the film.

[0098] In Comparative Examples 8 and 9, layer (B) was not provided, and a blend of modified polyolefin and polyurethane (solid content ratio of modified polyolefin / polyurethane=50 / 50 and 70 / 30, respectively) was examined as layer (C). However, it was confirmed that the non-polar modified polyolefin layer was localized at the deposition interface, reducing affinity with the deposition layer and resulting in a significant deterioration in oxygen permeability after deposition.

Claims

1. At least a substrate (A), A layer (B) made of a modified polyolefin resin; A layer (C) made of a urethane resin composition containing a urethane resin (c1); A laminate having The layer (B) is provided on the substrate (A), A laminate comprising the layer (C) on the layer (B).

2. 2. The laminate according to claim 1, further comprising a vapor-deposited layer (D) on said layer (C).

3. 2. The laminate according to claim 1, wherein the glass transition temperature of the urethane resin composition is in the range of 5 to 95° C.

4. The laminate according to claim 1 , wherein the urethane resin composition further contains an aqueous medium (c2).

5. 2. The laminate according to claim 1, wherein the urethane resin (c1) is made from a polyester polyol.

6. 6. The laminate according to claim 5, wherein the concentration of aromatic rings derived from the polyester polyol in the urethane resin (c1) is in the range of 1 to 4 mmol / g.

7. 6. The laminate according to claim 5, wherein the raw material of the polyester polyol contains diethylene glycol and ethylene glycol in the range of 9 to 40% by mass.

8. 2. The laminate according to claim 1, wherein the urethane bond concentration of the urethane resin (c1) is in the range of 1.5 to 4 mmol / g.

9. The laminate according to claim 1, wherein the acid value of the urethane resin (c1) is in the range of 15 to 45 mg KOH / g.

10. 2. The laminate according to claim 1, wherein the layer (C) has a surface wetting tension of 40 mN / m or more.

11. 2. The laminate according to claim 1, wherein the modified polyolefin resin contains 80% by mass or more of ethylene and propylene in total as raw materials.

12. An article comprising the laminate according to any one of claims 1 to 11.

Citation Information

Patent Citations

  • Vapor-deposition-film laminate and method for manufacturing the same

    JP2011031526A